Controllable Preparation of Bioactive Glass Ceramic - Chen, Yan; Pan, Yusong (Asian Journal of Chemistry, 2014)
Bioactive glass ceramic has shown excellent biocompatibility, bioactivity and biodegradability properties. It was one of the most promising substitute materials of artificial joint. In this paper, the controllable preparation research process of bioactive glass ceramics, including development history and preparation technologies have been reviewed. Based on the recent research, the further research should be focused on improving mechanical properties, osteogenetic mechanism and biological response to in vivo testing.